ON THE EQUIVALENCE OF THE COKRIGING AND KRIGING SYSTEMS - Subramanyam A.; Pandalai H.S. (My University, 2004)
Simple cokriging of components of a p-dimensional second-order stationary random process is considered. Necessary and sufficient conditions under which simple cokriging is equivalent to simple kriging are given. Essentially this condition requires that it should be possible to express the cross-covariance at any lag series h using the cross-covariance at |h|=0 and the auto-covariance at lag series h. The mosaic model, multicolocated kriging and the linear model of coregionalization are examined in this context. A data analytic method to examine whether simple kriging of components of a multivariate random process is equivalent to its cokriging is given
Keywords: COKRIGING; KRIGING; INTRINSIC COREGIONALIZATION; SPATIAL ORTHOGONALITY; MOSAIC MODEL